2018
DOI: 10.21037/jtd.2017.12.53
|View full text |Cite
|
Sign up to set email alerts
|

Locally-advanced non-small cell lung cancer: shall immunotherapy be a new chance?

Abstract: Locally advanced non-small cell lung cancer (NSCLC) represents approximately one third of presentations at diagnosis. Most patients are judged non-surgical due to disease extension, and chemo-radiotherapy still represents the standard therapeutic option, with unsatisfactory results in terms of overall survival (OS) despite advances in staging and radiation therapy planning and delivery. Immunotherapy, and in particular immune-checkpoint inhibitors targeting the PD-1/PD-L1 axis, gained wide popularity for NSCLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Reanalysis of survival from recurrence after CRT to death also showed that patients who used ICI had a significantly better survival compared to those who did not (HR: 0.19 [95% CI: 0.068–0.55], P = 0.002). There is an increasing body of preclinical and clinical data regarding the radiotherapy‐induced immunomodulatory effects in the local tumor microenvironment, supporting the combination strategy . Radiotherapy modifies the tumor microenvironment, including enhanced antigen presentation, and the upregulation of tumor programmed death ligand‐1 and major histocompatibility complex class I expression .…”
Section: Discussionmentioning
confidence: 99%
“…Reanalysis of survival from recurrence after CRT to death also showed that patients who used ICI had a significantly better survival compared to those who did not (HR: 0.19 [95% CI: 0.068–0.55], P = 0.002). There is an increasing body of preclinical and clinical data regarding the radiotherapy‐induced immunomodulatory effects in the local tumor microenvironment, supporting the combination strategy . Radiotherapy modifies the tumor microenvironment, including enhanced antigen presentation, and the upregulation of tumor programmed death ligand‐1 and major histocompatibility complex class I expression .…”
Section: Discussionmentioning
confidence: 99%
“…Minimising radiation induced lung injury is the major potential clinical benefit of the individualised approach of FA planning for the NSCLC patients. Along with the wider availability and proven benefit of immunotherapy for lung cancer patients, there are ongoing trials investigating concurrent immunotherapy and radio-chemotherapy [6] , [25] . The lung toxicity profile of multimodality treatments is yet to be established, as the combination of different treatment modalities could potentially be more toxic.…”
Section: Discussionmentioning
confidence: 99%
“…Immune checkpoint inhibitors (ICIs) are a novel class of drugs for the treatment of NSCLC. [6][7][8] ICIs activate the host's immune cells, especially T cells, to target specific tumor cells. ICIs include programmed cell death protein 1 (PD-1), programmed death ligand 1 (PD-L1), and cytotoxic T lymphocyte-associated antigen 4 (CTLA-4) inhibitors, and have revolutionized the NSCLC treatment landscape.…”
Section: Introductionmentioning
confidence: 99%